Behavior modification principles and procedures - Miltenberger, Raymond G. (Wadsworth/Thomson learning, 2000)
In this revision of Miltenberger's popular BEHAVIOR MODIFICATION, students first master the principles and concepts of behavior modification before they move on to the procedures. This approach gives students a chance to understand WHY they are going through the procedures before they actually do them. The author presents a precise, step-by-step scientific approach to explain human behavior, using numerous case studies to help illustrate the key principles. Miltenberger's first edition built a reputation for currency of scholarship and an engaging writing style-characterized by interesting examples, ample graphs and illustrations, flawless definitions, and a clear organization. Professors and students especially appreciate Miltenberger's end-of-chapter applications and misapplications of behavioral principles that give students a feel for using what they've learned.